Psychiatric manifestations of paraneoplastic syndromes - M. Lemos; A. Lourenço; M. Ribeiro (European Psychiatry, 2022)
Introduction Paraneoplastic syndromes (PS) result from indirect effects of neoplasms. In 50% of the cases the symptoms precede the diagnosis and run independently. PS may involve the peripheral or central nervous system, resulting in symptoms from sensory neuropathies to several neuropsychiatric manifestations.